2021
DOI: 10.1017/jfm.2020.1044
|View full text |Cite
|
Sign up to set email alerts
|

Dilatational-wave-induced aerodynamic cooling in transitional hypersonic boundary layers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
4
7
0
Order By: Relevance
“…The experiments were performed in the Mach 6 hypersonic wind tunnel at Peking University (Zhu et al 2018). The tunnel is a blow-down hypersonic facility, which can provide Mach 6 air flow through a relatively short axisymmetric nozzle, with a 160 mm exit diameter and open-jet test section.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were performed in the Mach 6 hypersonic wind tunnel at Peking University (Zhu et al 2018). The tunnel is a blow-down hypersonic facility, which can provide Mach 6 air flow through a relatively short axisymmetric nozzle, with a 160 mm exit diameter and open-jet test section.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Second-mode instability is inviscid and behaves as acoustic waves reflecting between the solid wall and the sonic line in hypersonic boundary layers, and plays an increasingly important role as the Mach number increases (Fedorov 2011). Zhu et al (2018) identified that the second-mode instability is correlated with high-frequency fluid compression and expansion, and results in an additional heating peak before transition. This newly discovered mechanism of dilatational heating differs from the traditional theory that aerodynamic heating is due mainly to viscous dissipation, and has been described as a new principle for aerodynamic heating (Sun & Oran 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, respectively [28]. The admittance of the acoustic metasurface is a complex number and can be expressed as A = |A|e iθ , where |A| denotes the admittance magnitude and θ denotes the admittance phase.…”
Section: Fig 1 Schematic Illustration Of the Acoustic Metasurface With Subwavelength Groovesmentioning
confidence: 99%
“…More updated progresses could be found in Refs. [25][26][27][28]. Recently, Zhao et al [31] expanded the research subjects by introducing the acoustic metasurface concept.…”
Section: Introductionmentioning
confidence: 99%